Subphthalocyanines as Efficient Photosensitizers with Nanomolar Photodynamic Activity against Cancer Cells - Demuth, Jiri; Gallego, Lucia; Kozlikova, Magdalena; Machacek, Miloslav; Kucera, Radim; Torres, Tomas; Martinez-Diaz, M Victoria; Novakova, Veronika (Journal of medicinal chemistry, 2021)
Because cancer is the second leading cause of death globally, investigation of new photosensitizers for photodynamic therapy is highly desirable. In this work, different peripherally substituted subphthalocyanines (SubPcs) with either a benzocrown moiety (CE-) or a tyrosine methyl ester (Tyr-) as the axial ligand have been prepared. Target SubPcs showed high ΦΔ values, >0.50 in EtOH. Both CE- and Tyr- moieties increased substantially the hydrophilicity of the compounds (log P = 1.79-2.63, n-octanol/PBS). Uptake to cells, subcellular localization, and monitoring of the progression of cell death over time are described. Improved spectroscopic behavior of the CE- series in cell culture medium resulted in higher photodynamic activity versus that of the Tyr- series. In particular, the peripherally triethylsulfanyl SubPc-CE exhibited extraordinarily low EC50 values of 2.3 and 4.4 nM after light activation and high TC50 values of 14.49 and 5.25 μM (i.e., dark toxicity without activation) on SK-MEL-28 and HeLa cells, respectively, which rank it among the best photosensitizers ever.
Keywords: Photosensitizing Agents; nádorové buněčné linie; Photochemotherapy; Isoindoles; fotosenzibilizující látky; isoindoly; Cell Line, Tumor; Humans; fotochemoterapie; lidé; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou